Prom mom : a novel [large type] - Lippman, Laura, 1959- (Harper Large Print, an imprint of HarperCollinsPublishers, 2023)
Drawn back to Baltimore where she is known as "Prom Mom"--The girl who allegedly killed her baby on the night of the prom after her date, Joe Simpson, abandoned her--Amber Glass is unable to stay away from Joe and vice versa, until he asks her to help him do the unthinkable